Peran Keterlibatan Orang Tua dalam Menumbuhkan Kepekaan Sosial Anak di Desa Sepit Kecamatan Keruak Kabupaten Lombok Timur - Muhammad Zoher Hilmi; Andika Apriawan (Peneliti.net, 2021)
Research Objectives 1) To describe the way parents in cultivating children's social sensitivity in Sepit village, 2) To describe the form of parental involvement in fostering children's social sensitivity in Sepit village, 3) To analyze the impact of parental involvement in fostering children's social sensitivity in the village Tongs. Meanwhile, the results of this study are as follows: The way parents in cultivating children's social sensitivity in Sepit village is by introducing children to several traditions or customs carried out by the community. The form of parental involvement in fostering children's social sensitivity in Sepit village is through invitations, group ties, actions, warnings or stories and education. While the impact of parental involvement in growing children's social sensitivity in Sepit village, parental involvement in growing children's social sensitivity in Sepit village has a very positive impact. This can be seen from the various activities carried out by the community, children participating in these activities.